Transferts interlinguistiques dans des tâches d'écart d'information chez des apprenants de FLE - Elena Coşereanu (Recherches en didactique des langues et des cultures)
The idea that learners use of their L1 or other languages learned fulfils a vital role in the process of L2 acquisition tends to be widely accepted today in language acquisition research. In this study, we sought to observe the influence that the L1 or other languages were likely to have on the production and communication strategies of learners of French as a foreign language (FFL). We conducted a study where we observed and compared the language performance of learners of FFL at the completion of several information gap tasks realized in dyads under two conditions of synchronous communication: spoken face-to-face or internet chat.Our findings support the idea that we can establish a typology of interlinguistic transfer phenomena, based on the degree of transformation undergone by the linguistic structure resulting from the L1 or other language when it is mobilized by the learner. They also suggest that the achievement of interaction tasks in conditions of autonomy is a situation that can be particularly revealing of how learners' interlanguage is influenced by their L1 or other languages, and this can bring to light the strategies used by learners to support their skills in the L2 from resources derived from their knowledge of other languages.